2023
DOI: 10.1371/journal.pone.0280338
|View full text |Cite
|
Sign up to set email alerts
|

Association between recent COVID-19 diagnosis, depression and anxiety symptoms among slum residents in Kampala, Uganda

Abstract: Background Despite the known link between poor living conditions and mental health, there has been little research on the mental health of slum dwellers worldwide. Although the Coronavirus disease 2019 (COVID-19) pandemic has led to an increase in mental health issues, little focus has been given to the impact on slum dwellers. The study aimed to investigate the association between recent COVID-19 diagnosis and the risk of depression and anxiety symptoms among people living in an urban slum in Uganda. Method… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
1
0
0
Order By: Relevance
“…This finding is consistent with other systematic studies, which also reported anxiety as one of the impacts of COVID-19 (30,31). The study highlights that the pandemic has led to an increase in anxiety among individuals, indicating a rise in mental health problems during this period (32). This implies mental health problem increase during the pandemic.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with other systematic studies, which also reported anxiety as one of the impacts of COVID-19 (30,31). The study highlights that the pandemic has led to an increase in anxiety among individuals, indicating a rise in mental health problems during this period (32). This implies mental health problem increase during the pandemic.…”
Section: Discussionsupporting
confidence: 91%